A Multidisciplinary Approach Of An Adult With Unirateral Cleft Lip And Palate - Neslihan Üçüncü; Ayşe Gülşen; Emel Yücel-Eroğlu (Galenos Yayinevi, 1999)
In this article, some orthodontic-orthognathic-prothetic treatment applications for a adult patient with unilateral cleft lip and palate were reported. The class III relationship, the negative overjet and the dental malalignment which existed before the treatment was traeted by orthodontic treatment. Orthognathic approaches were applied to treat the mandibular protrusion, maxillary retrüsion and concave profile. Prothetic treatment methods were used for the spaces in the dental arc and retention. After the treatment, it was observed that the multidisciplinary approach that was applied to the adult patient resulted in a good occlusion and the facial aesthetic was satisfactory.